A five year study of maternal mortality in Mandya district, Karnataka, India - Ramachandra, Pradeep Musale; Manohar, Rangaswamy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal mortality is a quality health care of that area. We planned a study on maternal mortality ratio (MMR) to understand the causes leading to maternal mortality in Mandya district, Karnataka, India after the introduction of national rural health scheme in past five years. Methods: It is a retrospective analysis of case records. We collected records of MMR occurred from Jan 2011 to Dec 2015 over a period of five years from district health office. Results: MMR from Jan 2011 to Dec 2015 is 38.25/lakh live births the same was 106.9 (in 2001-05) and 95.89 (2006-10). MMR commonly seen between 20-29years and most of them died within 24 hours of admission. Post-partum haemorrage (PPH), eclampsia and amniotic embolism are still the leading causes, anaemia plays a major role (10% direct and 37.5% indirect cause) of maternal mortality. Conclusions: Introduction of NRHM certainly helped to reduce MMR in our district. MMR by Anaemia, PPH and eclampsia are largely preventable on early recognition and aggressive treatment by skilled birth attendants.